Firefighters Brand Personality: A Model Proposal (Dimensión Empresarial, 2018)
The objective of this research is to apply the brand personality theory, and with this identify and study the personality traits that citizens assign to the Chilean Fire Companies. Through a comprehensive literature review and the application of semi-structured questionnaires, in-depth interviews and focus groups, a theoretical model of brand personality of the firemen is proposed. All these procedures comply with the requirements of content validity. It is obtained, as a result, the “Firefighter Brand Personality model (FFBP)”, which has adequate levels of content validity, is multidimensional in nature, of reflexive type and second order, and is composed of the dimensions: a) competence; b) exciting; c) social; d) sincerity; e) helpful; and f) generosity.ResumenEl objetivo de esta investigación es aplicar la teoría de personalidad de marca, y con esto identificar y estudiar los rasgos de personalidad que los ciudadanos asignan a las Compañías de Bomberos de Chile. Mediante una exhaustiva revisión de la literatura y la aplicación de cuestionarios semi-estructurados, entrevistas en profundidad y focus groups, se propone un modelo teórico de personalidad de marca de los bomberos. Todos estos procedimientos cumplen con los requisitos de la validez de contenido. Como resultado se obtiene el modelo “Firefighter Brand Personality (FFBP)”, el cual tiene adecuados niveles de validez de contenido, es de naturaleza multidimensional, de tipo reflexivo y segundo orden, y está compuesto por las dimensiones: a) competencia; b) emocionante; c) social; d) sinceridad; e) servicial; y f) generosidad.ResumoO objetivo desta pesquisa é aplicar a teoria da personalidade da marca e, com isso, identificar e estudar os traços de personalidade que os cidadãos atribuem às departamentos de bombeiros do Chile. Por meio de uma revisão exaustiva da literatura e da aplicação de questionários semi-estruturados, entrevistas em profundidade e grupos focais, propõe-se um modelo teórico de personalidade de marca de bombeiros. Todos esses procedimentos atendem aos requisitos de validade de conteúdo. Como resultado, obtém-se o modelo “Firefighter Brand Personality” (FFBP), que possui níveis adequados de validade de conteúdo, é de natureza multidimensional, de tipo reflexivo e de segunda ordem, sendo composto pelas seguintes dimensões: a) competência; b) excitante; c) social; d) sinceridade; e) útil; e f) generosidade.
Keywords: Brand Personality; Volunteer; Model; Firemen.